Circulating proteomic panels for risk stratification of intracranial aneurysm and its rupture. Issue 2 (3rd January 2022) - Xiong, Yueting; Zheng, Yongtao; Yan, Yan; Yao, Jun; Liu, Hebin; Shen, Fenglin; Kong, Siyuan; Yang, Shuang; Yan, Guoquan; Zhao, Huanhuan; Zhou, Xinwen; Hu, Jia; et al.
Abstract: The prevalence of intracranial aneurysm (IA) is increasing, and the consequences of its rupture are severe. This study aimed to reveal specific, sensitive, and non‐invasive biomarkers for diagnosis and classification of ruptured and unruptured IA, to benefit the development of novel treatment strategies and therapeutics altering the course of the disease. We first assembled an extensive candidate biomarker bank of IA, comprising up to 717 proteins, based on altered proteins discovered in the current tissue and serum proteomic analysis, as well as from previous studies. Mass spectrometry assays for hundreds of biomarkers were efficiently designed using our proposed deep learning‐based method, termed DeepPRM. A total of 113 potential markers were further quantitated in serum cohort I ( n = 212) & II ( n = 32). Combined with a machine‐learning‐based pipeline, we built two sets of biomarker combinations (P6 & P8) to accurately distinguish IA from healthy controls (accuracy: 87.50%) or classify IA rupture patients (accuracy: 91.67%) upon evaluation in the external validation set ( n = 32). This extensive circulating biomarker development study provides valuable knowledge about IA biomarkers. Synopsis: This study constructed a comprehensive mass spectrometry‐based proteomics strategy for serum protein biomarker discovery for intracranial aneurysm (IA). The presented workflow integrates the results of current proteome research and previously reported studies, yielding a comprehensive serum protein biomarker bank of IA. A highly efficient and timesaving PRM assay approach (DeepPRM) is proposed to facilitate targeted quantification of large‐scale candidate proteins. Machine learning on the serum proteome distinguishes IA from healthy controls with an accuracy of 87.50%, and ruptured from unruptured IA with an accuracy of 91.67%. Abstract : This study constructed a comprehensive mass spectrometry‐based proteomics strategy for serum protein biomarker discovery for intracranial aneurysm (IA).